Functions and Potential Applications of Circular RNAs in Cancer Stem Cells - Feng, Ziyang; Meng, Shujuan; Zhou, Hecheng; Xu, Zihao; Tang, Ying; Li, Peiyao; Liu, Changhong; Huang, Yongkai; Wu, Minghua (Frontiers in Oncology, 2019)
Circular RNAs (circRNAs) were discovered in the 1970s, but they have drawn increasing attention in recent years. Currently, we know that circRNAs are not “wrongly spliced” during transcription but play important roles in the initiation and development of various diseases, including cancers. Recently, a growing number of studies have suggested that cancer stem cells (CSCs) may contribute to the origination and maintenance of cancers. This review briefly introduces the major functions of circRNAs, including interacting with other noncoding RNAs, competing with pre-mRNA splicing, binding with proteins to form a scaffold, promoting protein nuclear translocation and even translating proteins in a cap-independent manner. Furthermore, we describe the regulatory mechanism of circRNAs in CSC phenotypes and discuss the potential clinical applications of circRNAs in CSC-targeted therapy, including functioning as new biomarkers, acting as vaccines and breaking the therapeutic resistance of CSCs. Finally, we discuss the major limitations and challenges in the field, which will be beneficial for the future clinical use of circRNAs.